Crop Raiding Status by Assamese Monkeys (Macaca assamensis) along the Kaligandaki River, Western Nepal - Ghimire, Suvas Chandra; Chalise, Mukesh Kumar (Journal of Institute of Science and Technology, 2019)
A study on Assamese monkeys (Macaca assamensis) in Kaligandaki river basin at Ramdi of Palpa and Syangja districts of western Nepal was performed. The field study was conducted from February 2015 to January 2016 spending 1804 hours to explore the ecology and feeding behavior of Assamese macaque. The study mainly focused the Ramdi village area. A total of 24 individuals of Assamese monkeys were counted towards Palpa district and 18 individuals were counted towards Syangja district. Crop raiding status was examined each year by questionnaire survey method for local household villagers as well as direct observation by the researcher. It was found that maize (47.14 %) was the highest raided among the crops, followed by fruits (16.43 %), wheat (11.13 %), millet (5.72 %), rice (4.58 %), potato (4.27 %), lentil (4.07 %), mustard (1.26 %), pumpkin (1.14 %), bread (0.96 %), brown lentil (0.81 %), broad beans (0.80 %), sesame (0.60 %), black pulses (0.35 %), dal (0.20 %), cauliflower (0.14 %), tomato (0.1 %), egg (0.1 %), samosa (0.1 %) and gram (0.1%).